Sick of Your Poor Neighborhood? - Linea Hasager; Mia Jørgensen (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2021)
Does living in a low-income neighborhood have negative health consequences? We document causal neighborhood effects on health by exploiting a Spatial Dispersal Policy that quasi-randomly resettled refugees across neighborhoods from 1986-1998. The risk of developing a lifestyle related disease before 2018 increased by 5.1 percent for those allocated to the poorest third of neighborhoods compared with those in the richest third of neighborhoods. Our results suggest that interaction with neighbors and the characteristics of the immediate environment are important determinants for health outcomes. Differences in health care access, ethnic networks, and individual labor market outcomes cannot explain our findings.
Keywords: J15; I12; I14; I31; 330; health inequality; refugee dispersal policy; lifestyle related diseases; neighborhood effects